Phase separation and histone epigenetics in genome regulation. Issue 1 (February 2021) - Harrison, Reed E.S.; Weng, Kegui; Wang, Yingxiao; Peng, Qin
Highlights: Summary of the properties driving phase separation and the examples of phase separation relevant for genome regulation. Discussion on epigenetics of histones that mediate chromatin structure and organization. Discussion on epigenetics of histones that mediate transcriptional regulation. Discussion on how epigenetics and phase-separation interact to drive genome regulation. Abstract: Liquid-liquid phase separation is increasingly recognized as a phenomenon that affects cell behavior. For example, phase separation of transcription factors and coactivators has been shown to drive efficient transcription. For many years, phase separation of intracellular components has been observed; however, only recently have researchers been able to garner functional significance from such events. Inspired from recent literature that describes phase separation of chromatin in a histone-dependent manner, we review the role and effect of phase separation and histone epigenetics in regulating the genome and discuss how these phenomena can be leveraged to control cell behavior.